"I Do the Dishes; You Mow the Lawn": Gender Effects in Stereotypically Feminine Negotiation Tasks. Issue 1 (25th November 2016) - Demoulin, Stéphanie; Teixeira, Cátia P.
Research on gender effects in negotiation has largely relied on stereotypically masculine negotiation paradigms (e.g., selling a car). Globally, though with relatively weak effects sizes, this research shows that women tend to underperform men in negotiations. The present research examines gender effects in negotiations involving typically female-related topics. Specifically, we examine perceptions and performance of mixed negotiating dyads. We manipulate the topic of the negotiation between dyads: typically feminine (i.e., household duties) vs. neutral (i.e., organization of a debate). Results show an interaction between the gender of the negotiator and the negotiation topic. Among men, the topic of negotiation impacts neither perceptions nor negotiation performance. Among women, in contrast, aspirations and performance decrease in the stereotypically feminine negotiation condition compared to the neutral one. Furthermore, this effect of topic of negotiation on performance among women is mediated by (lower) aspirations of women in the feminine topic condition. We discuss results in light of recent research on gender and negotiation, as well as of broader theories such as role congruity and stereotype threat.